Disaster-Safe Schools in Indonesia: The Disaster Mitigation Activity Program (ProMB) in Early Childhood Education - Ningrum, Mallevi; Sri Setyowati; Ruqoyyah Fitri; Eka Cahya Maulidiyah; Wulan Patria Saroinsong; Dhian Ghowinda Luh Safitri (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
Indonesia is a country that is prone to natural disasters, so it is necessary to take preventive measures against the dangers that occur in order to carry out self-rescue efforts. However, curriculum integration with disaster mitigation activities has not been widely implemented by PAUD institutions. The purpose of this study was to conduct a survey on the implementation of ProMB in early childhood education units. This research was conducted using a quantitative approach with a survey method. The respondents of this study were 234 teachers who teach at kindergarten level using an online questionnaire. The findings obtained were that teachers had designed learning with disaster mitigation activity content showing a score of 62.30%. ProMB can be implemented with supporting facilities such as 1) physical facilities; 2) supporting equipment; 3) training of educators and education personnel on understanding natural disaster simulations; 4) educational game tools; and 5) cooperation with external parties. Teachers' teaching experience has a significant influence on the quality of learning about the implementation of ProMB. This study concludes that the implementation of ProMB has been carried out by teachers in a structured manner. Further research needs to integrate disaster mitigation material with the curriculum of educational units and provide training facilities to teachers to improve their competence in teaching disaster mitigation material in a more enjoyable way.